The enlightenment of China's cultural soft power development on Ukraine - Chenlin, Chen (Економіка природокористування і сталий розвиток, 2018)
Cultural soft power is the overall influence and competitiveness of a country's culture. Enhancing the soft power of national culture has become a major strategic issue of each country all over the world. As the world’s second largest economy, the development of cultural industry and the promotion of Chinese culture has always been regarded as an important task, which has made good achievements in the development of China’s cultural soft power. Especially, in recent years, China's leaders have paid high attention to cultural soft power, which has produced cultural influence and attraction to a certain level internationally, and created a beautiful image of China at the same time. This paper makes a systematic analysis on the effect of the development of China's cultural soft power. By combining with the reality of the development of Ukraine's cultural soft power, this paper tries to put forward the way and strategies to develop Ukraine's cultural soft power, to improve policies and regulations, and to implement innovative development of Ukraine's culture on the basis of studying the development measures and beneficial experience of China's cultural soft power. In this way, Ukraine's cultural industry will be stronger and larger, and then, the system of Ukraine’s culture dissemination to foreign countries will be established. М'яка сила культури – це загальний вплив на конкурентоспроможність культури країни. Посилення м’якої сили національної культури стало головним стратегічним питанням кожної країни у всьому світі. Будучи другою за величиною економікою в світі, розвиток культурної індустрії та просування китайської культури завжди розглядалося як важливе завдання для досягнення хороших успіхів у розвитку м’якої сили КНР. Особливо останнім часом лідери Китаю приділяють велику увагу культурній м’якій силі, яка призвела до культурного впливу та привабливості як на локальному, так і міжнародному рівні, і одночасно створила прекрасний імідж Китаю. Цей документ систематично аналізує вплив розвитку м’якої сили культури України. У поєднанні з реальністю розвитку м’якої сили культури України цей документ намагається висувати шляхи та стратегії її розвитку, поліпшити політику і правила та впроваджувати інноваційний розвиток української культури на основі вивчення заходів розвитку та корисного досвіду м’якої сили культури КНР. Таким чином, українська культурна індустрія буде сильнішою та могутнішою, а згодом сформується така система, яка сприятиме розповсюдженню української культури в інші країни. 文化软实力是一个国家文化所体现出来的总体影响力和竞争力。增强国家文化软实力，己 经成为摆在世界各个国家面前的重大战略课题。中国作为世界第二大经济体，一直以来把发 展本国文化产业和推广中国文化作为重要任务，在发展国家文化软实力中取得了有目共睹的 成绩。特别是近年来，中国国家领导人高度重视文化软实力的发展，在国际上产生了一定的 文化影响力和文化吸引力，同时也塑造出了中国美好的国家形象。本文对中国文化软实力的 发展成效进行了比较系统地分析，在研究中国文化软实力发展措施和有益经验的基础上，结 合乌克兰文化软实力发展的实际，尝试提出发展乌克兰文化软实力的具体路径和战略，完善 相关政策法规，实现乌克兰文化创新性发展。由此，将乌克兰文化产业做强、做大，并构建乌 克兰对外文化传播体系。